Comparative Proteomic Analysis Revealed the Mechanism of Tea Tree Oil Targeting Lipid Metabolism and Antioxidant System to Protect Hepatopancreatic Health in Macrobrachium rosenbergii - Liu, Mingyang; Sun, Cunxin; Zheng, Xiaochuan; Zhou, Qunlan; Liu, Bo; Zhou, Yifan; Xu, Pao; Liu, Bo (Frontiers in Immunology, 2022)
Tea tree oil (TTO) is a pure natural plant essential oil. The studies evaluated the hepatopancreas lipid metabolism and antioxidant efficacy of Macrobrachium rosenbergii fed with 0 (CT group) and 100 mg/kg TTO (TT group) by label-free quantification proteomic analysis. Compared to the CT group, the TT group improved growth performance and increased the survival rate after stress. Dietary TTO also decreased hemolymph AST and ALT activities and decreased hepatopancreatic vacuolation. At the same time, hepatopancreas lipids droplets and hemolymph lipids (TG, TC, LDL-C) were decreased, and the peroxidation products content (MDA, LPO, 4-HNE) was also decreased. In addition, the levels of hepatopancreas antioxidant enzymes (T-AOC, CAT, and SOD) were increased in the TT group. With proteomic analysis, a total of 151 differentially expressed proteins (DEPs) (99 up-regulated and 52 down-regulated) were identified in the hepatopancreas. Kyoto Encyclopedia of Genes and Genomes (KEGG) and protein-protein interaction analysis showed that the 16 DEPs have interactions, which are mainly involved in the pathways related to lipid metabolism (fatty acid biosynthesis, fatty acid metabolism, glycerophospholipid metabolism) and redox reaction (cytochrome P450 enzyme systems). Furthermore, the mRNA expression of 15 proteins followed the proteomic analysis with qRT-PCR validation. Pearson correlation analysis showed that fatty acids and glycerophospholipid metabolism-related proteins were highly correlated to peroxide content, glycerophospholipid metabolism, and cytochrome P450 system-related proteins (CYP1A1, GSTT1, GPX4) were highly correlated to AST and ALT. Additionally, GPX4 is closely related to peroxide content and antioxidant enzyme activity. Our results revealed that TTO plays a protective role in the hepatopancreas targeting the critical enzymes and antioxidant reactions in lipid metabolism.